A Hidden Dynamic: Examining the Impact of Fear on Mental Health Officers' Decisions to Use Powers of Compulsory Detention. Issue 4 (21st August 2020) - Allen, Sophie; McCusker, Pearse
Abstract : Informed by literature identifying the role of fear in decision making processes, the study upon which this paper is based sought to explore Mental Health Officers' (MHOs) experiences of fear and whether this influences their decisions to use powers of compulsory detention under the Mental Health (Care and Treatment) (Scotland) Act (Scottish Government 2003). Semi-structured interviews exploring the experience of fear in mental health assessments were undertaken with eight MHOs employed by a Scottish Local Authority and findings indicated that it had a marked impact on MHO decision making. Two central themes emerged: first, a fear of doing harm to service users, their families or the wider public though making the 'wrong' decision; second, fear of public and professional scrutiny, should any such harm arise. The findings raise a number of recommendations for policy and practice in the statutory mental health field, in particular, the importance of acknowledging fear and identifying strategies to manage it in training and post qualifying practice for MHOs and equivalent roles in the UK and other jurisdictions. The findings also add weight to calls for additional research exploring the MHO role.